MMP-2 atua no desenvolvimento dentário e na remodelação óssea durante a erupção dentária - Sandoval, Nathália Gonring (2016)
Tooth development results from a highly coordinated epithelial-mesenchyme interaction in which mesenchyme cells originate the dental papilla and dental follicle, while ectodermal cells originate the enamel organ. Simultaneously, bone tissue is formed around the developing tooth, trapping it in a bony crypt. Tooth eruption requires the resorption of the coronal part of the bony crypt, followed by degradation of the lamina propria, most likely by metalloproteinases (MMPs) activity. Objectives: The aim of this research was to determine MMP-2 expression in the dental germ cells (ameloblasts, odontoblasts, dental papilla and dental follicle) and surrounding tissues (alveolar bone and lamina propria) of rat molars throughout the eruptive process. Material and Methods: A total of 24 rats (4,6,9,11,14 and 16 days old) were used in this study. MMP-2 was detected through immunohistochemistry. A qualitative analysis was performed to investigate the expression of MMP-2 in the dental germ cells, lamina propria, and coronal and basal regions of the bony crypt. Results: MMP-2 expression was observed in the dental papilla cells, dental follicle, ameloblasts, odontoblasts and bone cells from the coronal and basal regions of the bony crypt. MMP-2 was also detected in the lamina propria during the mucosal penetration stage of tooth eruption. Conclusion: We conclude that MMP-2 may be important for the extracellular matrix rearrangement necessary for tooth development and secretion of its mineralized tissues. We also conclude that MMP-2 may play a role in the extensive tissue remodeling during the intra-and-extra-osseous phases of the tooth eruption process.